دور المعاملات الإلكترونية في حوكمة إبرام الصفقات العمومية - إيمان دمبري (My University, 2018)
تضافرت الجهود لإصلاح المنظومة القانونية للصفقات العمومية في الجزائر بما يساير التطورات العالمية و انسجاما مع الالتزامات الدولية التي أخذتها على عاتقها حول محاربة الفساد والوقاية منه، وذلك بإدراج مقتضيات الحوكمة وتدعيم مبادئها في إبرام الصفقات العمومية. و لعل من أهم الإصلاحات و التي تكرس لحوكمة جيدة في هذا الإطار هي المعاملات الإلكترونية في مجال الصفقات العمومية، وذلك من خلال إدخال وسائل التكنولوجيا الحديثة واستعمالها كوسيلة للاتصال وتبادل المعلومات و الوثائق و إبرام الصفقات العمومية إلكترونيا، لذلك يسلط هذا المقال الضوء على الدور الإيجابي لهذه المعاملات في تحقيق حوكمة جيدة لإبرام الصفقات العمومية. Efforts have been made to reform the legal system of public procurement in Algeria in line with international developments and in line with the international commitments made by Algeria to combat and prevent corruption by incorporating the requirements of governance and consolidating its principles in the system of procurement. One of the most important reforms to good governance in this context is electronic transactions in the field of public procurement, through the introduction of modern technology and its use as a means of communication and exchange of information and documents as well as the conclusion of public procurement electronically, so this article was an attempt to highlight electronic transactions and highlight their positive role in achieving good governance for the conclusion of public procurement.
The role of electronic transactions in the governance of concluding public procurements